Assessing Synovitis and Bone Erosion With Apparent Diffusion Coefficient in Early Stage of Rheumatoid Arthritis. Issue 5 (September 2017) - Qu, Jin; Lei, Xinwei; Zhan, Ying; Li, Huixia; Zhang, Yu
Abstract : Purpose: The aim of this study was to assess the value of apparent diffusion coefficient (ADC) in distinguishing synovitis from joint fluid and bone erosion from cysts. Methods: Twenty-eight patients with suspected rheumatoid arthritis underwent diffusion-weighted imaging and pre– and post–contrast-enhanced magnetic resonance imaging. The mean ADC values were compared between synovitis and joint effusion and between bone erosion and cyst. Results: Mean ADC value of synovitis was significantly lower than that of the joint effusion (2.6 ± 0.37 × 10 −3 vs 1.63 ± 0.37 × 10 −3 mm 2 /s, P < 0.001; cutoff value 2.10 × 10 −3 mm 2 /s). Mean ADC value of bone erosion was significantly lower than that of the cysts (1.61 ± 0.39 × 10 −3 vs 2.39 ± 0.34 × 10 −3 mm 2 /s, P < 0.001; cutoff value 2.04 × 10 −3 mm 2 /s). Conclusion: Apparent diffusion coefficient can be used in differentiating between synovitis and joint effusion and between bone erosion and cysts.